2016
DOI: 10.1002/mrd.22657
|View full text |Cite
|
Sign up to set email alerts
|

Role of Wasp and the small GTPases RhoA, RhoB, and Cdc42 during capacitation and acrosome reaction in spermatozoa of English guinea pigs

Abstract: Cytoskeleton remodeling is necessary for capacitation and the acrosome reaction in spermatozoa. F-actin is located in the acrosome and equatorial region during capacitation, but is relocated in the post-acrosomal region during the acrosome reaction in spermatozoa from bull, rat, mice, and guinea pig. Actin polymerization and relocalization are generally regulated by small GTPases that activate Wasp protein, which coordinates with Arp2/3, profilin I, and profilin II to complete cytoskeletal remodeling. This seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 67 publications
0
12
0
1
Order By: Relevance
“…It prevents the premature fusion of the membranes and forms a scaffolding of proteins required for the normal course of the AR . Although some signaling pathways that could regulate the polymerization of actin in sperm have already been reported, they have not been related to the structuring in the apical region of the acrosome of the actin cytoskeleton . Our results show that, during capacitation, an actin cytoskeleton shaped like a headband or diadem is structured in the apical region of the acrosome, a cytoskeleton that was absent when Rac1 was inhibited, and although the quantity of F‐actin in the acrosome increases, the headband‐like structure was not observed (Figure A).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…It prevents the premature fusion of the membranes and forms a scaffolding of proteins required for the normal course of the AR . Although some signaling pathways that could regulate the polymerization of actin in sperm have already been reported, they have not been related to the structuring in the apical region of the acrosome of the actin cytoskeleton . Our results show that, during capacitation, an actin cytoskeleton shaped like a headband or diadem is structured in the apical region of the acrosome, a cytoskeleton that was absent when Rac1 was inhibited, and although the quantity of F‐actin in the acrosome increases, the headband‐like structure was not observed (Figure A).…”
Section: Discussionmentioning
confidence: 57%
“…13,32,33 Although some signaling pathways that could regulate the polymerization of actin in sperm have already been reported, they have not been related to the structuring in the apical region of the acrosome of the actin cytoskeleton. 21,27,32,34 Our results show that, during capacitation, an actin cytoskeleton shaped like a headband or diadem is structured in the apical region of the acrosome, a cytoskeleton that was absent when Rac1 was inhibited, and although the quantity of F-actin in the acrosome increases, the headband-like structure was not observed ( Figure 4A). Our data also indicate that the formation of this actin headband in the apical region of the acrosome can only be a consequence of the activity of Rac1.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…We examined the expression levels of the WASF1 gene and found that they were downregulated following YAP knockdown compared with those noted in the control cells. WASP proteins function as downstream effectors of the Rho GTPases and comprise two distinct subfamilies, which play important roles in cytoskeletal rearrangement and actin polymerization . All WASP subfamily members share a tripartite VCA (Verprolin homology, Cofilin homology, and Acidic) domain .…”
Section: Discussionmentioning
confidence: 99%